PENGARUH AUDIT TENURE DAN KANTOR AKUNTAN PUBLIK (KAP) SPESIALISASI MANUFAKTUR TERHADAP AUDIT REPORT LAG (ARL) - Irviona Chyntia Dewi; P. Basuki Hadiprajitno (Diponegoro Journal of Accounting, 2017)
The purpose of this study is analyze the influence of audit tenure and audit firm specialization of manufacturing towards audit report lag (ARL). The dependent variable of this study is audit report lag which is proxied as the number of days from the year-end to the date recorded as the opinion signature date in the auditors report and the independent variables of this study are audit tenure and audit firm specialization of manufacturing. Control variables in this study are restatements, leverage, return on assets, loss and corporate size.The populations of this research are all manufacture companies that listed in Indonesia Stock Exchange (BEI) in the period 2014-2015. The sample of this study consist of 98 companies listed in the Indonesia Stock Exchange (IDX) and submitted financial reports to Otoritas Jasa Keuangan in the period 2013-2015. The data that used in this research was secondary data from financial statement and independent auditor’s report of manufacturing companies. The samples of this research selected by using purposive sampling method. Model analysis using multiple linear regression analysis.The results of this study indicates that audit firm specialization of manufacturing has significant negatif influence towards audit report lag (ARL). However, audit tenure has positif influence and did not significant towards audit report lag (ARL). This result suggests the manufacture firms can reduce audit report lag (ARL) by hiring an audit firm specialization of manufacturing.